Propuesta de estrategias didácticas basadas en el método socrático para el proceso de enseñanza en la Filosofía en el primer año de bachillerato - Melendrez Fuentes, Rosa Elizabeth (2023)
The present investigative work called "Proposal of didactic strategies based on the Socratic Method for the teaching process in Philosophy in the first year of high school", aims to propose didactic strategies based on the Socratic method to improve the learning process of the subject of Philosophy in the students of the first year of high school, and respond to the educational needs that arise in the chair of Philosophy. The present investigation has a qualitative approach because it starts from an analysis of the applied instruments such as the questionnaire that will allow to know and identify what are the types of didactic strategies that teachers use to promote the learning of said subject, the same ones that allowed to carry out an analysis and interpretation to elaborate the respective conclusions and recommendations regarding the Socratic method as a didactic strategy in the teaching of Philosophy; the population and sampling were nonprobabilistic; Within the achievements achieved, students will be able to develop strategies that will allow them to have critical thinking, interpret, analyze, evaluate and argue an opinion of a text, a dialogue or a conversation.